2014
DOI: 10.1080/17405629.2014.890585
|View full text |Cite
|
Sign up to set email alerts
|

Emotion understanding: A cross-cultural comparison between Italian and German preschoolers

Abstract: This is an author version of the contribution published on:Questa è la versione dell'autore dell'opera: AbstractItaly and Germany belong to the Latin and the Germanic cultural cluster, respectively, and show e.g. diverse languages, religious practices, rearing styles and socialization goals. Given potential cultural differences in the developmental goals of independence and interdependence, the present work sought to explore developmental differences between German preschoolers understood that expressed and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 29 publications
2
44
0
2
Order By: Relevance
“…Thus, TEC results from the UK, Brazil, Switzerland, Norway, Denmark, Italy, Germany, and Peru reveal similar age changes (Bender et al, 2015;Karstad et al, 2016;Molina, Bulgarelli, Henning, & Aschersleben, 2014;Pons et al, 2004;Roazzi et al, 2009;Tenenbaum, Visscher, Pons, & Harris, 2004). However, findings for the age at which children from different cultural backgrounds understand the hiding of felt emotion have been mixed.…”
Section: Cultural Similarities and Differences In The Understanding Omentioning
confidence: 88%
See 2 more Smart Citations
“…Thus, TEC results from the UK, Brazil, Switzerland, Norway, Denmark, Italy, Germany, and Peru reveal similar age changes (Bender et al, 2015;Karstad et al, 2016;Molina, Bulgarelli, Henning, & Aschersleben, 2014;Pons et al, 2004;Roazzi et al, 2009;Tenenbaum, Visscher, Pons, & Harris, 2004). However, findings for the age at which children from different cultural backgrounds understand the hiding of felt emotion have been mixed.…”
Section: Cultural Similarities and Differences In The Understanding Omentioning
confidence: 88%
“…We compared this rank-order to those observed in three other samples: British children (Pons et al, 2003), German children, and Italian children (Molina et al, 2014), as shown in Table 1. The British and German cultures can be regarded as representative of individualistic cultures whereas the Chinese and Italian cultures can be regarded as representative of more collectivist cultures (See Table 1 for the size, age range, and mean age of each of the four samples).…”
Section: Cultural Differences In the Understanding Of Emotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies find a positive relationship between SES and better EU (Cutting & Dunn, 1999;Dunn & Brown, 1994), and other studies report no effect of SES on preschoolers' EU (Karstad, Wichstrom, Reinfjell, Belsky, & Berg-Nielsen, 2015;Molina, Bulgarelli, Henning, & Aschersleben, 2014). The majority of this research is dominated by research on WEIRD middle-class samples, i.e., samples from Western, Educated, Industrialized, Rich, and Democratic societies, which according Henrich, Heine, and Norenzayan (2010), may not be representative populations from which to make generalizations.…”
Section: Socioeconomic Differences In Children's Eumentioning
confidence: 99%
“…Although the limitations of representability, as discussed below, must be kept in mind, we believe that our findings are likely to be representative for the population of children with HA in Norway. Caution is needed when generalizing the results to populations in other countries, as emotion comprehension and the parents' awareness thereof are likely to differ between cultures (Molina, Bulgarelli, Henning, & Aschersleben, 2014).…”
Section: Parents' Estimation Of Their Child's Emotion Understandingmentioning
confidence: 99%